Influência do tipo de forno para cristalização do dissilicato de lítio na resistência de união ao cimento resinoso e na resistência flexural - Castro, Thácio de (2016)
The aim of this study was to evaluate the influence of the type of the furnace used in the crystallization of the lithium disilicate on the bond strength and flexural strength. Ceramic samples (n=10) were prepared for the control (crystallized on the Programat P300 furnace) and experimental groups (crystallized on FVPlus furnace) according to the tests. The bond strength of the groups was assessed by microshear test. The samples were prepared with blocks IPS e.max CAD associated with 4 resin cement cylinders with each 1mm² on the surface of each block. The microshear test was made in 2 times (24 hours: T0; 30 days storage in artificial saliva: T1). The flexural strength of the groups was assessed by 3 point bending test. IPS e.max sticks (20mm x 4mm x 1,2mm) were prepared (n=10) for the control and experimental groups. The samples were tested on EMIC machine. The results have undergone statistical analyses by T- test. The micro shear bond strength results showed no statistical difference between tested groups and intra groups, considering different storage time. There was no significant difference of 3 point bending test between groups. Although the limitations of this study, it is concluded that there is no difference in bond strength and flexural strength for lithium disilicate specimens independent of furnace type tested.